2015
DOI: 10.1021/acs.jpcb.5b07277
|View full text |Cite
|
Sign up to set email alerts
|

Complexation of Lysozyme with Sodium Poly(styrenesulfonate) via the Two-State and Non-Two-State Unfoldings of Lysozyme

Abstract: To provide an in-depth understanding of the complexation mechanism of protein and polyelectrolyte, a heating-cooling-reheating protocol was employed to study the unfolding and refolding behaviors of a model protein, lysozyme, in the presence of a negatively charged polyelectrolyte, sodium poly(styrenesulfonate) (PSS). It was found that, with elevated PSS concentration, a new state (state I) was first formed via a "two-state" conversion process and this state could further convert to a completely unfolded state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 66 publications
1
19
0
Order By: Relevance
“…Nevertheless, if the interactions between PSS and lysozyme responsible for the high density of the complexes are of hydrophobic nature they can be expected to have some effect on the conformation of the protein. In fact, Wu et al [40] recently showed that nearly charge stoichiometric complexes of lysozyme and linear PSS contain a large fraction of lysozyme in a state different from the native form. In a mixture with a PSS/lysozyme-charge ratio of 1.5 at 20 °C, where the non-native state completely dominated, the contents of α -helix and β -sheet was reported to be 18% and 30%, as compared to 36% and 14%, respectively, in the native state.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, if the interactions between PSS and lysozyme responsible for the high density of the complexes are of hydrophobic nature they can be expected to have some effect on the conformation of the protein. In fact, Wu et al [40] recently showed that nearly charge stoichiometric complexes of lysozyme and linear PSS contain a large fraction of lysozyme in a state different from the native form. In a mixture with a PSS/lysozyme-charge ratio of 1.5 at 20 °C, where the non-native state completely dominated, the contents of α -helix and β -sheet was reported to be 18% and 30%, as compared to 36% and 14%, respectively, in the native state.…”
Section: Resultsmentioning
confidence: 99%
“…In the present paper we investigate this further by studying the binding of lysozyme to sodium poly(styrenesulfonate) (PSS) microgel spheres by means of micropipette-assisted microscopy. PSS is known to interact electrostatically and hydrophobically with lysozyme [39,40,41] and with cationic surfactant micelles [42,43,44,45], in contrast to PA which is expected to display mainly electrostatic interactions. One motive behind the study is thus to investigate how the hydrophobic backbone of PSS affects the binding and aggregation of lysozyme in gels.…”
Section: Introductionmentioning
confidence: 99%
“…This may explain why a decrease in antiviral activity was noted with NIC solubilized in DMSO compared to NIC particles. Interactions between NIC and hLYS in the microenvironment may serve as a mechanism to disrupt this self-association and ensure availability of the electronegative functional groups, as lysozyme has been previously demonstrated to complex with negatively charged molecules [73] and a hydrophobic drug [74]. Given the physicochemical properties of NIC, both chargedbased and hydrophobic interactions with hLYS may be important.…”
Section: Discussionmentioning
confidence: 99%
“…At this specic temperature, the vibrational energy will disrupt the native conformation causing the protein to denature, thereby losing its tertiary structure. [28][29][30] Use of this approach allows assessment of ensilicated protein in powder and native/released protein in solution, indicating whether ensilicated protein has the mobility to unfold under heating/ freezing within its silica shell. Furthermore, varying the silica ratios used for ensilication would indicate the optimised silica to protein ratio required to render a protein thermally stabilised while allowing for the easiest possible release of the protein from the silica shell.…”
Section: Introductionmentioning
confidence: 99%
“…2.1.4 Detection of 29 Si aer release. The release mechanism is a sequence of several steps that allow the ensilicated material to be released.…”
Section: Introductionmentioning
confidence: 99%